African Studies Centres Around the World : A Network-Based Inventory - Fendler, Ute; Löhr, Doris (Akademische Verlagsgemeinschaft München AVM, 2022)
The book “African Studies Centres Around the World – A Network-Based Inventory” compiles a selection of contributions by the directors of eleven African Studies centres from four continents. They comprise Africa’s oldest centre on the continent, at the University of Cape Town, the European centres in Bordeaux, Lisbon and Hradec Králové and the two North American Universities of Florida and Indiana. Central and South America’s contributions to African Studies is represented by the centres in San José, Costa Rica, Santiago de Cuba and Salvador da Bahia, Brazil. The Asian centres are located at Jawaharlal University in Mumbai, India, and at Hankuk University of Foreign Studies in Seoul, South Korea. The eleven chapters show the very diverse history of the centres, explaining their different structures, underpinning the need for more exchange and collaborative research. The volume presents some aspects of the ongoing critical reflections on the historical and political development of African Studies in various parts of the world, disseminating first-hand knowledge while the chapters encourage to open the exchange and collaboration across regional, disciplinary and academic boundaries.
Keywords: African Studies; African Studies Centres; international collaboration; networks